Associated factors of REM sleep without atonia in younger (≤ 50 years) hospitalized psychiatric patients - Bušková, Jitka; Miletínová, Eva; Kliková, Monika; Bareš, Martin; Novák, Tomáš; Kosová, Jiřina; Stopková, Pavla; Kopřivová, Jana (BMC psychiatry, 2020)
BACKGROUND: Isolated REM sleep without atonia (RSWA) as a main polysomnograhic feature of REM sleep behaviour disorder (RBD) is thought to be a prodromal or subclinical state of the disease. RSWA/RBD occurence in psychiatric population is much more frequent than in general population but its associated factors are still not known. METHODS: We invited 88 psychiatry in-patients to undervent video-polysomnography. The visual scoring was focused on RSWA in submentales and flexores digitales superficiales muscles. This parametr was subsequently correlated mainly with age/gender, their medication and mental status. RESULTS: The RWSA was mostly still in normal range despite the fact, that selected psychiatry patients (≤ 50 years) were taking several classes of psychoactive medication. 3,6% had convincingly RBD, although 35.7% reported rare lifetime occurence of dream-enacting behaviour and 62.8% sporadic nightmares. We found correlation between RSWA and SNRI medication class (p = 0.015), specifically venlafaxine (p = 0.029) as well as quetiapine (p = 0.030). Another significant associated factors were current anxiety (p < 0.001) and depressive symptoms (p = 0.05), but we found no relation between RSWA and given diagnosis. CONLUCIONS: Isolated RSWA in younger psychiatry patients might be a result of multiple factors, including medication and current mental status but these factors are in most cases not sufficient to manifest RBD.
Keywords: Sleep, REM; porucha chování v REM spánku; Psychiatric patients; REM sleep behaviour disorder; polysomnografie; svalová hypotonie; Polysomnography; lidé; Humans; Antipsychotics; REM Sleep Behavior Disorder; Muscle Hypotonia; Antidepressants; REM sleep without atonia; Anxiety; spánek REM; Depression